Tradisi Naung Ri Ere: Telaah terhadap Nilai-Nilai Budaya Islam - Nur Ahsan Syakur,; Nurul Annisa, (Tumanurung: Jurnal Sejarah dan Budaya, 2025)
The community's understanding of the practice of its cultural traditions in each region has diversity which reflects the strong belief and trust that grows and develops among the community as supporters of a culture. This research focuses on studying the Islamic cultural values ​​of the Naung Ri Ere tradition in the community of Balassuka village, Kunciopao District, Gowa Regency. To explore the relationship between Islamic values ​​in this research, it is necessary to break it down into sub-problems, namely: How is the process of implementing the Naung Ri Ere tradition in the people of Balassuka Village, Kunciopao District, so that a link can be found between local traditions and Islamic cultural values. This research is descriptive-qualitative research using religious, historical, sociological and anthropological approaches. This research relies on the use of primary data with data collection techniques through field research, which comes from data from researchers' interviews with informants. Secondary data was obtained from reading sources and previous research that were relevant to this research. From the data obtained, proceed with data analysis such as data reduction, data presentation, and drawing conclusions. The results of the research can be concluded that the Naung Ri Ere tradition is a tradition that was carried out by the people of Balassuka Village before the arrival of Islam. People believe that carrying out this tradition can keep away unwanted things, especially for newlywed couples. It is best done the day after the wedding party. This tradition has stages of implementing the Naung Ri Ere tradition starting with preparing the equipment to be brought including Halasuji, Manuk Sikalabini, chicken eggs, Kaluku Lolo (young coconut), Golla Eja (brown sugar), Unti bulaeng (golden banana), and Kanre Tallu Rupa (three types of rice). There are Islamic cultural values ​​contained in the Naung Ri Ere tradition, namely: the values ​​of brotherhood, communication, spirituality, friendship, mutual help, religious values, and the value of gratitude. Implications of this research: for society, government and youth are expected to be able to preserve and maintain the values ​​contained in this tradition. The researcher also hopes that future researchers can develop this theme for further research because of course there are still many other aspects that need to be researched.